Derivatization, characterization and high-performance liquid chromatography-UV detection method for benomyl determination in wettable powder (benlate) - Özer, Metin; Aydın, Adnan; Özer, Lale (My University, 2006)
A pre-column derivatization method is developed for the determination of benomyl (1-butylcarbamoyl-2-benzimidazole methyl carbamate) in Benlate 50% wettable powder. Benomyl is converted to tetrabromomethyl-2-benzimidazolecarbamate (TBrMBC) by bromination of methyl2-benzimidazolecarbamate (MBC) after hydrolysis of benomyl in methanol. Benomyl is UV/HPLC-determined as TBrMBC derivative at 264 nm after separation on an ODS column with 85:15-methanol:water, maintaining a flowrate of 1 mL/min. The retention time of TBrMBC is longer than that of MBC, by which the detection of benomyl in Benlate is achieved more accurately. The method indicated good reproducibility with an average relative standard deviation (% RSD) of 0.76 for benomyl determination.
Keywords: Benomyl; pre-column derivatization; bromination; chromatography; fungicides